Ganoderma seychellensis nom. nov. (Ganodermataceae), a replacement name for Ganoderma insulare Ryvarden (2020) - Parihar, Arvind; Hembrom, Manoj Emanuel (Phytotaxa, 2025)
Ganoderma P. Karst. is an important genus in the family Polyporaceae. Ryvarden in the year 2020 described a new species of Ganoderma, based on a collection from Seychelles (East Africa), and named it as Ganoderma insulare Ryvarden (Ryvarden 2020). However, Ryvarden (2020) unintentionally missed the earlier validly published name Ganoderma insulare Har. & Pat. (Har. & Pat.1903), resulting in a nom. illegit., according to the Art. 53.1 of the International Code of Nomenclature for Algae, Fungi, and Plants (Turland et al. 2018).